The Analysis of Students’ Difficulties in Understanding Learning Concepts on Using Zoom Cloud Meeting in Virtual Classrooms - Agustin, Rury Ayu; Lina, Marisa Fran (Journal of English Teaching and Learning Issues, 2022)
Today many people are interested in implementing the concept of virtual classes, such as using Zoom Cloud Meetings for learning. Therefore, the authors are interested in discussing the difficulties of students in understanding learning activities using Zoom Cloud Meeting in virtual classes. The purposes include describing the kind of learning activities using Zoom Cloud Meeting in virtual classes and determining the students’ difficulties using Zoom Cloud Meeting in virtual classes. This study uses qualitative methods. The data collection techniques are interviewing ten respondents from the fifth-semester English Education Department of an Islamic University in Central Java, and the documentation. The results of this study indicate that learning by using zoom helps students and teachers meet virtually face-to-face. Zoom has various features that support the learning process, such as screen sharing, raising hand icons, chat comments, screen recording, and many other potential features. However, many students say that although Zoom has complete features, this application also has several shortcomings that become obstacles for students in understanding the concept of learning. These include limited-time usage and lag applications if the network or quota is insufficient. This study implied that Zoom Cloud Meeting makes the learning material not conveyed well; thus, the students' understanding becomes incomplete or partial.